PEMBINAAN KERAPIHAN ADMINISTRASI MENGGUNAKAN MICROSOFT OFFICE PADA IBU PKK KAVLING KAMBOJA SAGULUNG - Nia Ekawati; Rico Adrial (PUAN INDONESIA, 2022)
Information technology is currently well known by many people, such as children, teenagers, adults, and even parents nowadays, they must follow the latest technology, one of which is Microsoft office technology. Everyone knows this in schools, offices, and institutions. One of them is the women of Family Welfare Development (PKK) in the Kavling Kamboja RT 02 RW 03, Sei Pelungut Village, Sagulung District. PKK women in this area are quite active in various ways, of course, in the administrative process implemented at the Microsoft office, these PKK women must be orderly such as the correspondence process, making activity announcements, and managing household budgets in the PKK environment. Currently Microsoft office always makes new breakthroughs by updating its application to Microsoft office 2013. However, PKK women in the Kavling Kamboja want to learn administration in a simple way, so I try to use Microsoft office 2013. I use the application, because currently the process is correspondence is still asking for typing services, many PKK women still don't understand how to use Microsoft office. So the servants tried from the simple ones first, and the continuity of this activity could be understood by the PKK women.